Integrating Restorative Justice and the Principle of Islah in the Reform of Indonesia’s Criminal Justice System - Nur Khasanah; Stevani Ameliya Putri; Venita Wulandari; Syifa Az Zahra M. Iwan; Asrizal Saiin; Mashair Idris (NALAR FIQH: Jurnal Hukum Islam, 2026)
The Indonesian criminal justice system remains predominantly shaped by a retributive paradigm centered on formal punishment and incarceration, resulting in various structural problems, including prison overcrowding, the ineffectiveness of penal sanctions, victim marginalization, and the weak orientation toward social recovery and communal harmony.These conditions indicate the urgent need for a more humane, restorative, and substantive paradigm of criminal justice reform.